Modeling and analysis of frequency-variable 2–2 cement-based piezoelectric transducers. (1st March 2023) - Lan, Chengming; Wen, Lijie; Wang, Jianjun; Li, Weijie; Tang, Lihua
Abstract: The 2–2 cement-based piezoelectric transducers can be used as high-performance actuators and sensors. However, the existing designs with fixed electromechanical properties cannot meet some special application requirements, such as the tuning working frequency to achieve high precision monitoring purpose. To address this issue, a type of frequency-variable 2–2 cement-based piezoelectric transducers is proposed in this paper. Theoretical models of the proposed transducer are established, and the analytical solutions of its longitudinal vibration are obtained. The theoretical models are verified by comparing their results with those of the existing literature for some special examples, and with the finite element results for a special case. In addition, the effects of the tuning resistance, the ratio of piezoelectric layer numbers between the active and passive elements, the electrical connections of piezoelectric layers, and the total number of piezoelectric layers on the electromechanical properties of transducer are discussed. It is demonstrated that the proposed frequency-variable 2–2 cement-based piezoelectric transducers can obtain a large tunable bandwidth by adjusting the appropriate ratio of piezoelectric layer numbers between the active and passive elements and their electrical connections, which provides a theoretical basis for designing and optimizing this type of transducers.